Peranan Agen Pelayaran dalam Pengurusan Dokumen dan Pemesanan Kontainer pada PT. Naval Global Trans Cabang Belawan - Riko Ananda; Syarifur Ridho; Lilis, Lilis (Jurnal Transformasi Bisnis Digital, 2025)
This study aims to analyze the strategic role of the shipping agent, specifically PT. Naval Global Trans Belawan Branch, in ensuring the smooth flow of the maritime logistics chain. The shipping agent functions as a crucial intermediary coordinating contasiner distribution, bridging the interests of cargo owners, shipping companies, and the Belawan Port authority. The research utilizes a descriptive qualitative approach, with data collection performed through field observation and documentary study within the Belawan Port environment. The findings identify that the shipping agent holds broad responsibilities, commencing with container booking according to the required type and size, scheduling vessel arrivals and departures, managing customs and port documentation, and monitoring container movements (from the depot to loading onto the vessel). This role is highly instrumental in determining port throughput efficiency. However, in carrying out its functions, the shipping agent encounters several significant challenges. These constraints include limited container availability, disruptions in the port information system which is not yet optimally integrated, and dynamic changes in export-import regulations. These obstacles potentially cause operational delays and an increase in logistics costs. The study concludes by emphasizing the importance of better information technology integration between the shipping agent and the port authority. Furthermore, enhancing the quality of human resources (HR) through training and certification is key to ensuring that agents can respond to regulatory changes and operational challenges quickly and professionally.